(untitled) (CAHIERS MAGELLANES-NS, 2024)
The present study aimed to investigate the hypolipidemic effects of different doses of Kalanchoe pinnata in rats with hypercholesterolemia. Thirty albino rats weighing 180–200 g were divided into five groups. The first group (G1) served as the Normal control, while the second group (G2) was the Negative control, receiving a high fat diet (HFD) containing 2% cholesterol. The third group (G2) standard group received atorvastatin, fourth and fifth groups (G4 and G5) were also fed a 2% cholesterol diet but were supplemented with 250mg/kgbw and 500mg/kgbw, respectively, for 45 days. Hypercholesterolemic rats in G2 exhibited elevated lipid profiles, liver enzymes. Additionally, histological analysis of the heart, liver, tissues of G2 rats revealed pathological changes compared to G1. Administration of both doses of kalanchoe pinnata extracts to hypercholesterolemic rats in G4 and G5, respectively, led to improvements in lipid levels. Furthermore, histological examination of the heart and liver tissues showed restoration to nearly normal states, similar to those observed in G1.